2015
DOI: 10.1155/2015/858542
|View full text |Cite
|
Sign up to set email alerts
|

“New” Antigenic Targets and Methodological Approaches for Refining Laboratory Diagnosis of Antiphospholipid Syndrome

Abstract: Antiphospholipid antibodies (aPLs) are a heterogeneous group of antibodies directed against phospholipids or protein/phospholipid complexes. Currently, aPLs are assessed using either “solid-phase” assays that identify anticardiolipin antibodies and anti-β2-glycoprotein I antibodies or “liquid-phase” assay that identifies lupus anticoagulant. However, in the last few years, “new” antigenic targets and methodological approaches have been employed for refining laboratory diagnosis of antiphospholipid syndrome (AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 117 publications
(131 reference statements)
0
45
0
3
Order By: Relevance
“…Recently, autoantibodies against AnxA5 were found to be present in up to 17% of obstetric manifestations of APS cases, being the only serologic parameter significantly associated with miscarriage ( 19 ). However, due to inconsistent results among studies ( 8 ) the clinical correlation of autoantibodies against AnxA5 is still controversial discussed. Here, we detected moderate reactivity of IgM isotype antibodies against AnxA5, but we found considerably high reactivity of IgM isotype autoantibodies against AnxA2 and AnxA8 in the serum of our seronegative APS patient that suffered six miscarriages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, autoantibodies against AnxA5 were found to be present in up to 17% of obstetric manifestations of APS cases, being the only serologic parameter significantly associated with miscarriage ( 19 ). However, due to inconsistent results among studies ( 8 ) the clinical correlation of autoantibodies against AnxA5 is still controversial discussed. Here, we detected moderate reactivity of IgM isotype antibodies against AnxA5, but we found considerably high reactivity of IgM isotype autoantibodies against AnxA2 and AnxA8 in the serum of our seronegative APS patient that suffered six miscarriages.…”
Section: Discussionmentioning
confidence: 99%
“…The lupus anticoagulant test is the most predictive value for venous and arterial thrombosis in patients with suspected APS ( 7 ), whereas a high intermethod variability for aCL assays exists. This explains the low utility of aCL testing ( 8 ). The diagnostic value of the major epitope of ß2GPI is still controversial discussed due to potential conformational changes during the immunoassay which may lead to epitope masking effects.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, other lipids and other cofactors Fig. 1 The role of antiphospholipid antibodies and possible Bsecond hits^in the generation of thrombosis Clinic Rev Allerg Immunol have been identified and evaluated in APS patients [28,29]. In a recent meta-analysis [30], Reynaud et al reported that LA and aCL were significantly associated with venous thrombosis; in addition to these two biomarkers, there were significant associations between arterial thrombosis and the following antibodies, β2GPI, anti-prothrombin (aPT-the antibody that is likely responsible for positive lupus anticoagulant results), and anti-phosphatidylserine (aPS).…”
Section: Methods Used To Determine the Presence Of Aplmentioning
confidence: 99%
“…annexins A2, A4 and several others) ( Mussunoor and Murray, 2008;Wang and Lin, 2014;Wei et al, 2015), resistance to chemotherapy [annexin A13 (AnxA13)] (Reiske et al, 2010) to inflammation and autoimmunity (i.e. annexin A1, A2 or A5) (D'Acquisto et al, 2013;Misasi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%